ANALISIS PENGARUH VARIASI DIAMETER PULI DENGAN PERBEDAAN TAKARAN ADONAN PADA OLAHAN PENTOL TERHADAP KAPASITAS PRODUKSI - Adham Rifai, Hasif; Wulandari, Diah; Isnomo Abdi, Ferly; Riandadari, Dyah (Jurnal Rekayasa Mesin, 2025)
The ratio between chicken meat and flour in the dough affects its texture, including thickness, elasticity, and ease of molding. This study aims to analyze the effect of dough ratio variations and pulley diameter sizes on the performance of a meatball (pentol) molding machine. The pulleys used were 25.4 mm (1 inch), 50.8 mm (2 inch), and 76.2 mm (3 inch), with dough ratios of chicken meat to flour at 1:1, 1:2, and 2:1. The research employed an experimental method by testing each combination to measure the number of successful molds, failures, production capacity, and molding time. The results showed that the 1-inch pulley with a 1:1 dough ratio produced the highest success rate (15 pieces), the lowest failure rate (7 pieces), and the fastest molding time (3 minutes 15 seconds). Conversely, the 3-inch pulley resulted in the slowest process (6 minutes 40 seconds) and a lower success rate. Based on these findings, it can be concluded that the smallest pulley combined with a balanced dough ratio is the most effective in improving production efficiency. Keywords: Production efficiency, Chicken meatball, Pulley, Dough ratio